Pengaruh Penatausahaan Aset Tetap Tanah Terhadap Pengamanan Aset Tetap Tanah (Survei Pada OPD Pemerintah Kabupaten Bandung Barat) - Yuni Maudina; Arie Apriadi Nugraha (Jurusan Akuntansi Politeknik Negeri Bandung, 2022)
This research aims to determine the effect of Land Assets Administration on Land Assets Security in West Bandung Government. The population of this research is 45 Regional Apparatus Organization (OPD) in West Bandung Government, with purposive sampling of 25 OPD that had uncertified land and the respondent are 42 staff. This research is quantitave with a quantitative descriptive approach. Data obtained from quisionnaires with simple linear regression analysis using SPSS version 25. The result of this research show that the land assets administration has a significant and positive effect that is 84,1% on land assets security.